Intimate partner violence and challenges facing women living with HIV/AIDS in accessing antiretroviral treatment at Singida Regional Hospital, central Tanzania - Agnes Kosia; Deodatus Kakoko; Ave Maria Emilius Semakafu; Tumaini Nyamhanga; Gasto Frumence (Taylor & Francis Group, 2016)
Background: Human immunodeficiency virus (HIV) remains a global public health problem. Sub-Saharan Africa is the region most affected by HIV/AIDS in the world. Globally, and in Tanzania in particular, women are more affected by HIV/AIDS than men. Tanzania has been reported to be among the countries with the highest burden of intimate partner violence (IPV). This study explored the challenges facing women living with HIV/AIDS (LWHA) attending the care and treatment clinic (CTC) in Singida Regional Hospital in Tanzania. Design: A qualitative study was performed in which data were collected through in-depth interviews with 35 women LWHA who also experienced IPV. Content analysis was used to analyse the data. Results: The study findings showed that women LWHA experienced challenges from their male partners in the form of lack of fare to attend CTC, delayed attendance to CTC, verbal threats and intimidation, mistrust partner resulting in changed antiretroviral (ARV) dosing time. Also, systemic challenges such as malfunction of CD4 count testing apparatus contributed to mistrust from their male partners which led to IPV. Conclusion: In this study, women LWHA experienced IPV challenges that resulted in poor adherence to ARV medication and CTC attendance, as well as insufficient time to collect ARV medication. It is recommended that the government address systemic challenges faced by women LWHA, introduce multiple approaches to address the needs of women LWHA experiencing IPV, and develop strong policies to prevent IPV against women in Tanzania, regardless of their HIV status.